Sedimentary cycling of zinc and nickel and their isotopes on an upwelling margin: Implications for oceanic budgets and paleoenvironment proxies. (15th February 2023) - He, Zhiwei; Archer, Corey; Yang, Shouye; Vance, Derek
Abstract: Zinc and Ni are essential micronutrients whose stable isotope systematics in marine sediments represent promising, but still developing, tracers of past ocean chemistry and biology. Sediments from upwelling continental margins have been identified as important sinks for Zn and Ni, driven by high productivity, incorporation of the metals into cells and organic carbon burial. At present, however, our understanding of how Zn and Ni isotope composition of upwelling sediments reflects specific processes in the water column is incomplete. Here, we present coupled Zn and Ni abundance and isotope data for both solid phase and porewater in a series of sediment cores collected on a shelf-to-slope transect across an oxygen minimum zone (OMZ) from the southwest African margin off Namibia. Zinc/Al and Ni/Al ratios in Namibian margin sediments are elevated relative to the lithogenic background, by factors of 1.4–2.4 and 1.7–5.7, respectively. Systematic relationships between solid phase Zn and Ni concentrations and organic carbon accumulation corroborate the view that authigenic Zn and Ni are mainly delivered to these sediments via export production from the photic zone. Corrections for detrital Ni are sometimes substantial, but authigenic δ 60 Ni values are within uncertainty of the modern deep ocean, at 1.38 ± 0.18 ‰ (mean and 1SD, n = 42). Authigenic δ 66 Zn is more variable, at −0.09 to 0.50 ‰, at or below the value for the deep ocean average. This latter observation can be attributed to Zn isotope fractionation during sequestration into authigenic ZnS phases in the sediments, either quantitatively, or partially. Porewater systematics are more complex and the profiles do not necessarily reflect the redox state of the sediment-porewater system at the time of sampling, but rather characteristics inherited from more reducing conditions in a temporally heterogeneous system. Porewater zinc concentrations (30–369 nM) are much higher than the deep ocean and increase with depth beneath the sediment–water interface. Despite this prominent increase in Zn concentrations, δ 66 Zn is rather constant and lighter than the deep ocean average, at 0.18 ± 0.06 ‰ (mean and 1SD, n = 33). These observations are most consistent with the buffering of the small porewater pool by the dissolution of a previously formed sulfide phase. Porewater Ni concentrations are closer to the deep ocean, mostly at 5–15 nM. The lightest porewater isotope compositions (δ 60 Ni as low as 0.15 ‰) are consistent with a Mn-oxide source of Ni, whereas the heaviest isotope compositions (up to 1.76 ‰) clearly reflect uptake of light Ni into sulfide at depth within the sediment. Our data, for the largest upwelling site in the modern ocean, add to sparse data from the eastern Pacific, and confirm that upwelling margin sediments bury Ni that is close to the deep ocean in isotope composition, but Zn that is generally lighter. The data thus confirm the importance of such margins in setting the heavy isotope composition of oceanic Zn. Sediments from this kind of setting hold significant potential for the construction of records of past oceanic Ni isotopes.